"I Don't Want to Have a Weird Relationship with You, So I'm Trying": Relational Turning Points and Trajectories of Ex-Member Children and Their Member Parents in the Church of Jesus Christ of Latter-day Saints. Issue 4 (1st October 2020) - Worwood, Jared; Scharp, Kristina M.; Phillips, Kaitlin E.
ABSTRACT: Members of the Church of Jesus Christ of Latter-day Saints face a unique and often turbulent time in their relationship with their parent if the individual decides to leave the Church. To explore this phenomenon, we investigated the turning points and relational trajectories of children who have left the Church of Jesus Christ of Latter-day Saints and their interactions with their parents still active in the Church. Thirty emerging adult children were interviewed using the retrospective interviewing technique (RIT). Through turning point analysis, we identified nine overarching turning points: (1) open conversation, (2) restatement, (3) personal withdrawal, (4) confrontation, (5) conformity, (6) coming out, (7) moving out, (8) third-party events, and (9) boundaries and interference. Four relationship trajectories also emerged: (1) disrupted, (2) turbulent (3) declining, and(4) accelerating. Findings and theoretical implications are discussed.